2013
DOI: 10.1176/appi.ajp.2012.12040474
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Placebo Response in Antidepressant Clinical Trials

Abstract: Placebo response in clinical trials of antidepressant medications is substantial and increasing. High placebo response rates hamper efforts to detect signals of efficacy for new antidepressant medications, contributing to more failed trials and delaying the delivery of new treatments to market. Media reports seize upon increasing placebo response and modest advantages for active drugs as reasons to question the value of antidepressant medication, which may further stigmatize treatments for depression and dissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
219
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(226 citation statements)
references
References 61 publications
4
219
2
1
Order By: Relevance
“…31 The magnitude of the expectancy effect was apparent in a withdrawal study in which patients were injected with analgesia either in plain view or without the patient's knowledge in a cohort of healthy patients with experimentally induced pain and a second cohort of post-operative patients. In this evaluation, hidden injection resulted in significantly less pain relief in both experiments.…”
Section: Expectancy and The Pre-cebo Effectmentioning
confidence: 99%
“…31 The magnitude of the expectancy effect was apparent in a withdrawal study in which patients were injected with analgesia either in plain view or without the patient's knowledge in a cohort of healthy patients with experimentally induced pain and a second cohort of post-operative patients. In this evaluation, hidden injection resulted in significantly less pain relief in both experiments.…”
Section: Expectancy and The Pre-cebo Effectmentioning
confidence: 99%
“…The factors that affect placebo response in adults with depressive disorders (Sneed et al 2008;Papakostas and Fava 2009;Iovieno and Papakostas 2012;Rutherford et al 2012;Rutherford and Roose 2013) and anxiety disorders (Khan et al 2005;Stein et al 2006;Feltner et al 2009;Rutherford et al 2015) have been extensively evaluated; however, relatively limited information is available regarding the characterization of placebo response in pediatric patients with anxiety (Cohen et al 2010). In anxious adults, Stein et al (2006) have observed that placebo response for generalized anxiety disorder (GAD) was greater in studies conducted in Europe and in fixed-dose studies and was affected by lower baseline symptom severity, but was unaffected by gender and age.…”
Section: Introductionmentioning
confidence: 99%
“…However, more prosaic reasons for nonresponse are evident. Antidepressant response rates have declined by a couple of points every decade that they have been in use, such that the underlying dynamic is less likely to be pharmacological than related to the pattern of use [22]. The category of depression has widened over the past decades, and has incorporated less unwell patients with increasingly diverse sources of unhappiness.…”
Section: Introductionmentioning
confidence: 99%